Prospects of integration of virtual assistants in the process of teaching speaking to the beginner learners of the Japanese language - Victoria E. Marfina (RUDN Journal of Informatization in Education, 2023)
Problem statement . Most Japanese textbooks and methodical materials do not contain enough exercises for training productive skills of the students. Japanese Language Proficiency Test also does not include parts dedicated to writing and speaking abilities, which leads to teachers not paying attention to the development of these skills and students not being able to properly evaluate their level of performance. As a method of simplifying and making this training more engaging and motivating, virtual assistants, or intelligent personal assistants (IPA), can be introduced. The purposes of this research are to explore the ways of using the technology of virtual assistants to reenforce speaking performance of the beginner students in Japanese as a foreign language and to evaluate the technology’s readiness for integration. Methodology . In a pedagogical experiment took part 12 first-year students (10 female and 2 male), who attended a Japanese language class at the School of Young Philologist at the Faculty of Philology of Lomonosov Moscow State University, where they used Google Assistant for studying Japanese from December 2021 to April 2022 and then in September 2022. The analysis of theory and methodology, generalization of crucial scientific papers on the studied problem, processing of results were applied. Results. Personal assistant Google Assistant can be advised for training speaking among beginner learners. It can be applied in the form of four main types of exercises: asking for data, giving instructions to IPA, express desires (“wishlist”), conducting a dialog with a robot. Issues that can cause difficulties to students were listed. The results of the questionnaire revealed that students were grateful to have an opportunity to train speaking with a Japanese native speaker in a form of a virtual assistant and could easier track their progress. Conclusion. The use of the Google Assistant in the process of teaching speaking to the beginner learners of the Japanese language at the initial level is seen as highly promising and can be recommended for implementation in the educational process.